Fulfillment of employment social security rights as an employer’s legal obligation toward workers - Yuliansyah, Dedy; Iqbal, M.; Fitri, Rizky Aulia (Geuthèë Institute, Aceh, 2025)
Law No. 13 of 2003 concerning Employment serves as the primary statutory framework regulating employer-employee relations in Indonesia. The establishment of an employment relationship between employers and workers inherently generates specific legal obligations. Article 99, paragraph (1) of the Labor Law expressly guarantees that every worker, along with their family, is entitled to labor social security. This study seeks to critically examine the scope of employers' obligations in fulfilling the entitlement of workers to labor social security and to assess the legal ramifications of non-compliance. Employing an empirical juridical methodology, this research draws upon fieldwork data collected from relevant sources. The findings reveal that employers are legally mandated to enroll their workers in labor social security programs. However, in the city of Lhokseumawe, there remains a significant gap in compliance, with numerous employers failing to meet this obligation, thereby exposing them to potential administrative penalties and criminal sanctions. It is recommended that the Lhokseumawe branch of the Employment Social Security Agency (BPJS Ketenagakerjaan) strengthen its cooperation with other pertinent governmental bodies and amplify efforts in public outreach and legal education regarding employers' duties and the associated legal consequences. Furthermore, it is suggested that BPJS Ketenagakerjaan enhance the synchronization of company and workforce data with relevant institutions to facilitate more effective enforcement mechanisms.